Analysing and improving the performance and security of the cryptographically Generated Address (CGA) algorithm for mobile IPv6 networks - Qadir, Sana; Siddiqi, Mohammad Umar; Al-Khateeb, Khalid A. Saeed (International Journal of Network Security, 2015)
A Cryptographically Generated Address (CGA) is a self-certifying address that a node can generate when it joins a foreign network. Despite its advantages, generating CGAs is computationally expensive. This study examines the security and performance issues surrounding the CGA generation algorithm. It also scrutinizes the hash extension mechanism, different hash functions and how parallelism can be used to improve the performance of the CGA generation algorithm. It recommends imposing a minimal computational security of O(280), the use of HAVAL and parallelizing the algorithm with the main process spawning as many threads as one less than the number of cores available on the node.